A numerical implementation of the decomposition method for the Lienard equation - Kaya, D; El-Sayed, SM (Elsevier Science Inc, 2005)
In this study, a kind of explicit exact and numerical solutions to the Lienard equation is obtained, and the applications of the results to this equation has been compared with their known theoretical solution. This paper is particularly concerned with the Adomian decomposition method and the numerical results demonstrate that the new method is relatively accurate and easily implemented. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: the Adomian decomposition method; numerical solutions; the Lienard equation